House Democratic Caucus records - House Democratic Caucus (U.S.)
Correspondence, minutes of meetings, transcripts of meetings, caucus and House rules, reports, office files, handbooks, printed material, and other records pertaining to the proceedings of the caucus from the 67th through the 106th Congresses. Records relate primarily to caucus business such as the selection of the speaker of the House, committee chairmen, and members of House committees. Documents the work of two committees of the caucus, the Committee on Organization, Study, and Review, which promulgates and amends caucus rules, and when the Democrats are in the majority, the procedural rules of the House, and the Committee on Party Effectiveness, which establishes task forces to formulate broad party policy on national issues. Correspondents include caucus chairmen Victor H. Fazio, Richard A. Gephardt, Steny H. Hoyer, and Gillis William Long.
Organization of Democratic members of the U.S. House of Representatives. Established in 1796.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Fazio, Victor H. -- 1942- -- Correspondence; Gephardt, Richard A. -- 1941- -- Correspondence; Hoyer, Steny H. -- 1939- -- Correspondence; Long, Gillis William, -- 1923-1985 -- Correspondence; United States. -- Congress. -- House; Democratic Party (U.S.); House Democratic Caucus (U.S.). -- Committee on Organization, Study, and Review; House Democratic Caucus (U.S.). -- Committee on Party Effectiveness; United States -- Politics and government -- 20th century